2020
DOI: 10.1371/journal.pone.0228896
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Lake Mead National Recreation Area, USA: Occurrence and biological uptake

Abstract: Microplastics are an environmental contaminant of growing concern, but there is a lack of information about microplastic distribution, persistence, availability, and biological uptake in freshwater systems. This is especially true for large river systems like the Colorado River that spans multiple states through mostly rural and agricultural land use. This study characterized the quantity and morphology of microplastics in different environmental compartments in two large reservoirs along the Colorado River: L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 56 publications
8
49
1
1
Order By: Relevance
“…There were significant differences in the shape frequencies between the three sites (χ 2 = 8.095; chi-square test, p = 0.017). As reported by previous studies of microplastics pollutions in freshwater environments [34][35][36][37], we noted that fibers were the most abundant microplastic found in the samples from all three sites, whereas fragments were more commonly found in the samples from the sites (Costa Volpino and Lovere) with greater anthropogenic impact due to their proximity to wastewater inflow, as reported elsewhere [37].…”
Section: Totalsupporting
confidence: 88%
See 2 more Smart Citations
“…There were significant differences in the shape frequencies between the three sites (χ 2 = 8.095; chi-square test, p = 0.017). As reported by previous studies of microplastics pollutions in freshwater environments [34][35][36][37], we noted that fibers were the most abundant microplastic found in the samples from all three sites, whereas fragments were more commonly found in the samples from the sites (Costa Volpino and Lovere) with greater anthropogenic impact due to their proximity to wastewater inflow, as reported elsewhere [37].…”
Section: Totalsupporting
confidence: 88%
“…The chi-square test showed significant differences in the color frequencies between the three sites (χ 2 = 20.14; p = 0.002). The source of the blue particles is unclear, but their prevalence has been reported in previous studies [37,38].…”
Section: Totalmentioning
confidence: 91%
See 1 more Smart Citation
“…An abundance of microfibers have been found in aquatic (freshwater and marine) and terrestrial environments worldwide [7][8][9][10][11]. Recent studies have observed microplastics, the majority of which were microfibers, in the French Pyrenees, the Italian Alps and in snow samples from the Arctic [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Fibers are therefore more likely to interact with living cells that they encounter in the environment than beads and fragments. With our increasing awareness of their true ubiquity [9,23,58], further investigation of the effects of MPs, including fibers on phytoplankton communities, and potential bottom-up effects on aquatic food webs are warranted.…”
Section: Discussionmentioning
confidence: 99%